The effect of drug information service using leaflet media and medication reminder chart on adherence and blood pressure of hypertensive patients in primary health care - Yopi Rikmasari (Jurnal Ilmiah Farmasi, 2022)
Abstract Background: Treatment adherence is an important factor affecting blood pressure control in hypertensive patients. Intervention in pharmacy service can improve medication adherence and lower blood pressure.Objective: This study aimed to evaluate the effect of drug information service using leaflets and MRC on the level of patient compliance and lowering blood pressure.Method: The research design was a quasi-experimental pre-and post-design with control, the intervention group (n=20), and the control group (n=20). The patient adherence was measured using the MGLS questionnaire at the beginning and the end of the study. The intervention was performed by distributing a drug information leaflet and medication reminder chart (MRC). The differences of adherence pre and post-intervention were analyzed using paired t-test, while the differences in adherence and blood pressure between the control and the intervention group were analyzed using the Mann-Whitney test.Results: The results showed that there was a significant difference in adherence between pre and post-intervention (p<0.001). A significant difference was also found in the level of adherence between the control group and the intervention group (p<0.001). Whereas the decrease of systolic (p=0.396) and diastolic (p=0.564) blood pressure in the intervention group and control group was not different significantly.Conclusion: Drug information services using leaflets and MRCs affected patient adherence to medication, but did not interfere with the decrease of systolic and diastolic blood pressure.Keywords: leaflets, medication reminder chart, adherence, blood pressureIntisari Latar belakang: Kepatuhan pengobatan merupakan faktor penting yang mempengaruhi pengendalian tekanan darah pada pasien hipertensi. Intervensi dalam pelayanan kefarmasian diketahui dapat meningkatkan kepatuhan pengobatan dan menurunkan tekanan darah.Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh PIO (PIO) menggunakan media leaflet disertai pemberian MRC terhadap tingkat kepatuhan pasien dan penurunan tekanan darah.Metode: Desain penelitian berupa quasi-experimental dengan pre-test dan post-test design with control group. Subjek penelitian pada tiap kelompok intervensi (n=20) dan kelompok kontrol (n=20). Kepatuhan pasien diukur menggunakan kuesioner MGLS pada awal penelitian dan empat minggu setelah intervensi. Uji-t berpasangan digunakan untuk menganalisis perbedaan kepatuhan sebelum dan sesudah intervensi, sedangkan perbedaan kepatuhan dan perubahan tekanan darah antara kelompok intervensi dan kontrol dianalisis dengan uji mann-whitney.Hasil: Hasil penelitian memperlihatkan ada perbedaan kepatuhan yang signifikan antara sebelum dan sesudah mendapatkan intervensi (p<0,001). Selain itu, tingkat kepatuhan minum obat antara kelompok kontrol dan kelompok intervensi juga berbeda signifikan (p<0,001), sedangkan penurunan tekanan darah sistolik (p=0,396) dan tekanan darah diastolik (p=0,564) pada kelompok intervensi dan kelompok kontrol tidak terdapat perbedaan yang signifikan.  Kesimpulan: PIO menggunakan media leaflet disertai pemberian MRC mempengaruhi tingkat kepatuhan minum obat pasien, namun tidak memberikan pengaruh terhadap penurunan tekanan darah sistolik dan diastolik.Kata kunci: leaflet, medication reminder chart, kepatuhan, tekanan darah